The effects of protein concentration in proteomic study : effects of protein concentration on 2-dimensional gel electrophoresis - Mikael Snær Gíslason 1998- (2024)
Verkefni unnið á Vorönn 2024 In proteomics the identification of biomarkers is an important part of therapeutics and other health sciences. These biomarkers must be efficiently identified so that they can be characterized accurately, and their effects understood so that these proteins may be used to determine biological states or conditions. The amount of protein used in 2-Dimensional Gel Electrophoresis (2-DE) can differ based on proteins of interest. The effects of protein concentration on 2-DE were investigated in this experiment. Plasma samples were obtained from Arctic Therapeutics, and those samples treated by removing high abundance proteins (mainly albumin and IgG). These samples were cleaned in preparation for 2-DE by removing salts, phenols, and detergents. The amount of protein present in the cleaned plasma samples was acquired using the Bradford protein assay, and samples diluted to acquire a range from 5µg to 20 µg of protein present in loading volume. The proteins in the samples were separated through 2-DE. The SDS-PAGE gels were then stained using SYPRO™ Ruby protein gel stain, and imaged. These images were analysed using SameSpots™ software to identify the protein spots present on the gels. 6 images were analysed. The average normalized volumes of the spots did not show a statistically significant difference between protein amount groups. A small subjective loss of spot volume, at 5 µg of protein loaded, requires further study. The optimal protein concentration using SYPRO™ Ruby stain will depend on the expected amount of the protein of interest present in sample, as it will need to be above the 0.25 ng sensitivity lower bound of the stain. Í próteinmengjagreiningu eru greining lífmarka (e. biomarkers) mikilvægur hluti af lyfjameðferðum og öðrum heilbrigðisvísindum. Þessa lífmarka þarf að geta greint nákvæmlega og áhrif þeirra þarf að vita til að hægt sé að gera grein fyrir próteinum sem lýsa líffræðilegum kringumstæðum eða sjúkdómum. Magn próteins sem notað er í Tví-víðan rafdrátt(2-DE) ...